PENGEMBANGAN BISNIS BERBASIS KOMUNITAS: STUDI KASUS PEMASARAN OSB HERBAL - Akbar Zainudin; Jayadi; Yoyo Indah Gunawan (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The business environment is getting more dynamic. Globalization and the development of ICT (Internet Computers and Technology) have compelled companies to come up with innovative ways to connect customers effectively and efficiently. Creating a business community is one strategy to engage with consumers in the modern era. How effective the community is indeveloping a business is the key issue covered in this study, as demonstrated by the case of OSB Corporation. The theories, such as the definition of community, its constituent parts, and the procedures required to establish a community, are drawn from a variety of sources of literature. A case study approach is used in this qualitative research methodology. The herbal company OSB Corporation was the object of observations and interviews for the study. The study's results revealed that OSB Corporation's community had a significant impact on the company's sales